2017
DOI: 10.7554/elife.26371
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of Caspase-3 in facilitating Myc-induced genetic instability and carcinogenesis

Abstract: The mechanism for Myc-induced genetic instability is not well understood. Here we show that sublethal activation of Caspase-3 plays an essential, facilitative role in Myc-induced genomic instability and oncogenic transformation. Overexpression of Myc resulted in increased numbers of chromosome aberrations and γH2AX foci in non-transformed MCF10A human mammary epithelial cells. However, such increases were almost completely eliminated in isogenic cells with CASP3 gene ablation. Furthermore, we show that endonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
2
25
0
4
Order By: Relevance
“…Although MOMP and caspase-3 activation continue to be used as molecular markers of cell death, relatively recent studies demonstrated that, under some circumstances, instead of functioning as an apoptosis executioner, active caspase-3 plays an important role in carcinogenesis, metastasis, and therapy resistance (reviewed in [107,[112][113][114][115][116][117][118][119][120]). Caspase-3 can stimulate tumor cell growth through various routes.…”
Section: Role Of Caspase-3 In Tumor Repopulationmentioning
confidence: 99%
“…Although MOMP and caspase-3 activation continue to be used as molecular markers of cell death, relatively recent studies demonstrated that, under some circumstances, instead of functioning as an apoptosis executioner, active caspase-3 plays an important role in carcinogenesis, metastasis, and therapy resistance (reviewed in [107,[112][113][114][115][116][117][118][119][120]). Caspase-3 can stimulate tumor cell growth through various routes.…”
Section: Role Of Caspase-3 In Tumor Repopulationmentioning
confidence: 99%
“…In the second bucket, caspases cleave proteins to affect cell behaviour in the same cell (reviewed in [ 41 ]). Examples include sperm tail individualization in Drosophila [ 48 , 49 ], cleavage and activation of Wg-inhibitor Sgg to temper Wg signalling during Drosophila neurogenesis [ 50 ], cleavage and activation of endonuclease G to result in genome instability and oncogenic transformation in human cells [ 51 , 52 ], and cleavage of NANOG to allow mouse ESCs to differentiate [ 53 ]. In the last study, mouse NANOG was cleaved by caspase 9 in vitro , cleavage products were detected in differentiating ESCs, and the expression of a caspase-resistant NANOG prevented ESCs from differentiating.…”
Section: Cell Death Pathways Play Non-lethal Roles In Fate Changesmentioning
confidence: 99%
“…In 2015, Liu et al reported that MCF10A cells can survive with activated caspase 3 after exposure to low-dose 56 Fe ion irradiation (<3 Gys) [ 17 ]. Recently, the same group reported some MCF10A cells can escape cell death induced by Myc overexpression even though caspase 3 was activated [ 18 ]. Ichim et al found ABT-737, a prototypic BH3-mimetic compound, induced mitochondrial outer membrane permeabilization (MOMP) in a small fraction of mitochondria, leading to sublethal caspase 3 activation [ 19 ].…”
Section: Are There Other Examples Of Cells Surviving Caspase 3 Activimentioning
confidence: 99%